The effects of low dose leukotriene receptor antagonist therapy on airway remodeling and cysteinyl leukotriene expression in a mouse asthma model - Muz, M. Hamdi; Deveci, Figen; Bulut, Yasemin; Ilhan, Nevin; Yekeler, Hayrettin; Turgut, Teyfik (Nature Publishing Group, 2006)
Airway structural changes that occur in patients with asthma in response to persistent inflammation are termed airway remodeling. The cysteinyl leukotrienes (LTC4, D-4 and E-4) are known to play important roles in the pathobiology of asthma. To evaluate the effect of low dose montelukast (MK) on the development of airway remodeling using a chronic murine model of allergic airway inflammation with subepithelial fibrosis, BALB/c mice, after intraperitoneal ovalbumin (OVA) sensitization on days 0 and 14, received intranasal OVA periodically on days 14-75. MK treated mice received montelukast sodium intraperitoneally on days 26-75. The OVA sensitized/challenged mice developed an extensive eosinophil cell inflammatory response, goblet cell hyperplasia, mucus occlusion, and smooth muscle hypertrophy of the airways. In addition, in OVA sensitized/challenged mice, dense collagen deposition/fibrosis was seen throughout the lung interstitium surrounding the airways, blood vessels, and alveolar septae. The cysteinyl leukotriene 1 (CysLT1) receptor antagonist, MK significantly reduced the airway eosinophil infiltration, goblet cell hyperplasia, mucus occlusion, and lung fibrosis except airway smooth muscle hypertrophy in the OVA sensitized/challenged mice. The OVA sensitized/challenged mice had significantly increased epithelial desquamation compared with control mice. MK markedly reduced epithelial desquamation of airways in OVA/MK treated animals compared with OVA sensitized/challenged mice. MK treatment did not affect the levels of CysLT in lung tissue. Our results show that the important role of cysteinyl leukotrienes in the pathogenesis of asthma. Lower dose of CysLT1 receptor antagonism has a significant anti-inflammatory effect on allergen-induced lung inflammation and fibrosis but not airway smooth muscle hypertrophy in an animal model of asthma.
Keywords: anti-asthmatic agents; asthma; leukotriene antagonists; leukotrienes; montelukast; SRS-A